Development of innovation ecosystem and infrastructure of HEIs of the Republic of Kazakhstan - Sitenko, D.A.; Yessengeldina, A.S. (BUKETOV BUSINESS REVIEW, 2018)
The article considers the development of innovation ecosystem and innovation infrastructure in higher educational institutions of the Republic of Kazakhstan. The concept of an innovation ecosystem is becoming increasingly popular among scientists from different countries. Innovation ecosystem can be created within the framework of the university in order to reveal its innovative potential. The article considers the concept of an innovation ecosystem, its input and output streams. The authors present a model of an innovation ecosystem, which main elements are the scientific sector, innovation infrastructure, high-tech production, venture capital and start-ups. The active interaction of structural elements contributes to the functioning of the entire ecosystem. The article examines the foreign experience of functioning of various ecosystem participants on the example of the Massachusetts Institute of Technology (USA), which is distinguished by high innovation activity. The authors disclose the formation of an innovation infrastructure at the universities of the Republic of Kazakhstan, on which basis an innovation ecosystem will be formed in the future. Various elements of the innovation infrastructure that are involved in different stages of the commercialization of innovation are considered. The main tasks of functioning of commercialization offices at higher educational institutions of the republic are determined. Recommendations are given on the formation of innovation infrastructure in the framework of the innovation ecosystem and the transfer of technology at higher educational institutions of the republic.